LIVING A STRESSOR-FREE DAILY LIFE: PREVALENCE AND PSYCHOSOCIAL CORRELATES. (11th November 2018) - Almeida, D M; Chai, H Won; Joo, S; Sin, N; Charles, S T
Abstract: Daily stressors such as interpersonal tensions, work and family demands have been shown to be important predictors of poor health. However, much is less known about individuals who do not experience any stressors. How many adults report living a "stressor-free life", who are they, and is this beneficial? To answer these questions, we used data from the National Studies of Daily Experiences (NSDE) to calculate the prevalence of adults who reported no daily stressors over the course of 8 consecutive days. Data were comprised of 20, 188 daily interviews from 2, 804 adults ages 25–85. Results indicated that 9.7% of adults reported no stressors over the 8 days. These stressor-free individuals were more likely to be older, male, less-educated, and lower-income, compared to those who reported stressors. Stressor-free adults were also less likely to report positive events in their daily lives. Discussion will focus on the potential benefits of daily stress.